Novel metal chelating molecules with anticancer activity. Striking effect of the imidazole substitution of the histidine–pyridine–histidine system. Issue 17 (1st September 2015) - Ali, Taha F.S.; Iwamaru, Kana; Ciftci, Halil Ibrahim; Koga, Ryoko; Matsumoto, Masahiro; Oba, Yasunori; Kurosaki, Hiromasa; Fujita, Mikako; Okamoto, Yoshinari; Umezawa, Kazuo; Nakao, Mitsuyoshi; Hide, Takuichiro; et al.
Graphical abstract: Abstract: Previously we have reported a metal chelating histidine–pyridine–histidine system possessing a trityl group on the histidine imidazole, namely HPH-2Trt, which induces apoptosis in human pancreatic adenocarcinoma AsPC-1 cells. Herein the influence of the imidazole substitution of HPH-2Trt was examined. Five related compounds, HPH-1Trt, HPH-2Bzl, HPH-1Bzl, HPH-2Me, and HPH-1Me were newly synthesized and screened for their activity against AsPC-1 and brain tumor cells U87 and U251. HPH-1Trt and HPH-2Trt were highly active among the tested HPH compounds. In vitro DNA cleavage assay showed both HPH-1Trt and HPH-2Trt completely disintegrate pUC19 DNA. The introduction of trityl group decisively potentiated the activity.